Changing course in sustainable urban transport : an illustrated guide - Hickman, R; Framer, P; Breithaupt, M; Saxena, S (Asian Development Bank, 2011)
This illustrated guide provides a rich collection of images of sustainable urban transport initiatives from around the world. It considers the transport problems evident in many cities in Asia, including high levels of energy consumption, carbon dioxide emissions, congestion, road casualties, urban sprawl, and social exclusion. The projections are that these worseing trends are set to continue. A change in course is recommended, with a much clearer focus on urban planning, traffic demand management, public transit, non-motorized transport, streescape design, road planning, low-emission vehicles, and freight planning. This new paradigm for sustainable urban transport can support a much better quality of urban life in our cities in Asia.